Vulnerability Assessment and Spatio-Temporal Dynamics Analysis of Agricultural Flood in China - Liu, Yinong; Zheng, Jiaxi; Lu, Honggang; Li, Xijian (Frontiers in Environmental Science, 2022)
Flood is one of the main problems faced by agricultural production in China. The research of agriculture’s floods vulnerability is the premise of scientifically dealing with floods. Based on the vulnerability assessment framework of “sensitivity-exposure-adaptability,” this paper selects 14 evaluation indicators from three aspects: sensitivity, exposure, adaptability, and the index weights which are determined by the entropy weight method to evaluate the sensitivity, resilience, and vulnerability of flood In terms of time, China’s overall flood vulnerability shows a trend of increasing first and then decreasing. From a spatial point of view, the number of highly vulnerable areas is relatively small which are mainly concentrated in Henan, Hubei, Anhui and other provinces, and most areas of the country are at low and mild levels. From the factor analysis model, the main contributing factors of agricultural flood exposure, sensitivity and adaptability are soil erosion control area, forest coverage rate, total reservoir capacity and total power of agricultural machinery. Therefore, controlling soil erosion, increasing forest coverage, further improving water conservancy facilities and strengthening agricultural mechanization level are the keys to reduce vulnerability of agricultural floods.